PEMANFAATAN BLOG SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Abdillah, Rustam; Joyoatmojo, Soetarno; Noviani, Leny (Department of Economics Education, Universitas Sebelas Maret, 2017)
The objective of research was to improve the learning achievement of negotiation and confirmation matter in the students of State Vocational High School 1 of Sukoharjo through using blog as learning media. This study was a classroom action research (CAR). This research was taken place in two cycles in nine meetings, with duration of 2 x 45 minutes for each meeting, and each cycles consisted of planning, acting, observing, and reflecting. The subject of research was the 11th Marketing 1 Graders of State Vocational High School 1 of Sukoharjo in the school year of 2014/2015, consisting of 33 students. Techniques of collecting data used were observation, test, field note, interview, and documentation. Technique analyse data is quantitative analysis, analysis qualitative, analyse comparability. The result of research showed that the utilization of blog could evidently improve learning achievement. It could be seen from the increase in the students’ learning outcome score from the mean class score of 71.69 in pre cycle to 83.83 in cycle I (increasing by 12.14 points) and from the learning passing score of 45.45% in pre cycle to 87.87% in cycle II (increasing by 42.42%). Meanwhile, for the learning outcome in cycle II, the mean class score increased by 1.43 points (from 83.83 in cycle I to 85.26 in cycle II) and the passing score by 6.07% (from 87.87% in cycle I to 93.94% in cycle II). Thus, it could be concluded that the utilization of blog as learning media to improve learning achievement had achieved the expected result in this research, in which the where each has achieved indicators reached by >75%.